Pelatihan Soft Skills Dan Pendampingan Siswa-Siswi SMK Di Kota Bogor Untuk Persiapan Memasuki Dunia Kerja - Ade Tuti Turistiati; Hafizh Faikar Agung Ramadhan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2019)
Graduates of Vocational High School (SMK) are prepared to work in public/private sectors, or work independently as entrepreneurs. The students are given hard skills based on their chosen majors and soft skills. However, the needs for soft skills are often less considered. This soft skills training program and mentoring for students of SMK in Bogor city aims to make students understand the importance of soft skills. The students are expected to practice applying/using soft skills that support them in finding/creating jobs opportunities; write application letters; write interesting, informative, and effective Curriculum Vitae (CV).  They are also expected to be self-confident to face a job interview. This program was followed by the 3rd graders of SMKN 1 and representatives of vocational school students in Bogor city, leaders and teachers of SMKN 1 Bogor. The training was divided into 2 batches; each batch consisted of 75 participants. After training and practicing, students were given the opportunity to consult directly (face to face) with facilitators, and seek for information and guidance through WhatsApp facilities and e-mails. The result of training and mentoring shows that the students understand the importance of soft skills such as communication skills, self-confidence, respect, open-mindedness, and honesty in a working environment and daily life.